The Influence of Servant Leadership and Organizational Climate on Employee Performance Through Affective Commitment as an Intervening Variabel (Study on Health Workers of Kumala Siwi Mijen Kudus Public Hospital) - Rizkia Prima Rahayu; Intan Ratna Wati (PT. Publikasiku Academic Solution, 2023)
Hospital is an integral part of the entire health care system that serves patients with various types of services. Health problems have a big role in improving people's standard of living. The spearhead of the hospital, namely health workers, consists of various professions that work collaboratively. Health worker performance refers to the extent to which health workers carry out their roles based on work expertise and efficiently achieve hospital goals. This study aims to examine how the influence of servant leadership and organizational climate on employee performance through affective commitment as an intervening variable. The research study was conducted at Kumala Siwi Mijen Kudus Public Hospital. The method used in this study is quantitative, namely using a representative sample to answer each statement submitted and using a questionnaire to collect research data. The research sample was 152 as health workers other than doctors at Kumala Siwi Mijen Public Hospital with a minimum working period of two years. The research analysis tool uses the AMOS 22.00 software with the SEM (Structural Equation Modeling) method. The results showed that servant leadership had no significant effect on the performance of health workers with a p-value of 0.689 (H1 was rejected). There is a significant influence of organizational climate on the performance of health workers with a p-value of 0.006 (H2 accepted). There is a significant influence of servant leadership on affective commitment with a p-value of 0.001 (H3 accepted). There is a significant influence of organizational climate on affective commitment with a p-value of 0.022 (H4 accepted). There is a significant effect of affective commitment on the performance of health workers with a p-value of 0.025 (H5 accepted). The conclusion is that affective commitment can be a mediating variable between servant leadership on the performance of health workers with an indirect effect value of 0.120 compared to a direct effect of 0.066. Then affective commitment does not mediate between organizational climate and the performance of health workers because the value of the direct effect is 0.318 greater, compared to the indirect effect of 0.073.